Pelatihan Desain Grafis sebagai Media Pemberdayaan Ekonomi Remaja Masjid Jakarta Islamic Centre - Johan Hendri Prasetyo; Widi Astuti; Lia Mazia; Fajar Sarasati; Jeri Dabi; Safira Maharani; Nabil Hanif Leksmono; Danang Rusdawindra Samiaji; Dennis Fathurahman (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Digitalization and the millennial era in Indonesia brought an effect to the competition in all industrial, commercial and non-commercial sectors that includes at the Islamic Youth Council of Jakarta Islamic Center which is known as Madaris JIC. By the advancement of digitalization which increases rapidly, has forced Madaris JIC to adjust with these conditions in order to develop the economy of the organization and its members. The obstacles that need to be faced by Madaris JIC is the lack of understanding in the use of graphic design applications which applied in products, packaging and posters in an effort to support economic empowerment within the organization. This became an urgent matter which one of that is graphic design education. Therefore, lecturers and students from Digital Business Study Program at the University of Nusa Mandiri (UNM) performed community service with aim to assist Madaris JIC youth to strengthen the economy of the organization and its members. The method used in this service is a persuasive lecture. This kind of service activity helps the participants to look for new ideas and use it to their products so as to improve their economy. The results of this assistance activity can increase the economy by 80% even though the selling price has increased due to additional operational costs in printing packaging designs that do not affect sales within the Madaris JIC environment. This activity also helps spread Madaris JIC da'wah through more creative and innovative product designs, packaging and da'wah posters so that it has an impact on Madaris JIC's brand awareness among the general public.